The Relationship between Information Literacy Competence and Library Users' Information-Seeking Behavior at the Library of the Padang Health Polytechnic, Ministry of Health - Puteri Salsabila; Desriyeni Desriyeni (Darul Yasin Al Sys, 2026)
The rapid expansion of information technology has broadened access to digital information resources; however, users do not always possess adequate competence to locate, evaluate, and use information effectively. This condition underscores the importance of information literacy as a key competency shaping information-seeking behavior in academic library contexts. This study aims to examine the relationship between information literacy competence and information-seeking behavior among users of the Library of Padang Health Polytechnic, Ministry of Health. A quantitative correlational design was employed, involving 99 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed through descriptive statistics and Spearman Rank correlation. The findings show that users’ information literacy competence was categorized as very high (mean = 3.32), while their information-seeking behavior was categorized as high (mean = 3.20). Correlation analysis revealed a positive and significant relationship between information literacy competence and information-seeking behavior (r = 0.595; p < 0.001). These findings indicate that higher information literacy competence is associated with more effective information-seeking behavior. The study contributes to the literature on academic library services by demonstrating the relevance of information literacy in supporting effective access to and use of information. Practically, the findings highlight the need to strengthen information literacy programs to improve library service quality and support students’ academic success.